(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The paper examined the strategies used by the security division of Federal University Dutse, Jigawa State in combating theft. It tried to understands the strategies used by the university security division in combating theft, A total of 356 respondents were selected as sample size from the university security division using total coverage. 356 sample were selected for quantitative data, the quantitative data collected were processed using Statistical Package for Social Sciences (SPSS), with the findings presented in frequency distribution tables and percentages. The findings revealed that the security division has made strides in the prevention and control of theft through efficient strategies such as patrol and guards, access control systems, criminal investigation, faculty security outpost. In light of these findings, the study recommends that the Federal University Dutse management should invest in advanced security technology, such as CCTV cameras and access control systems, to improve surveillance and monitoring. The University Security Division should also conduct regular patrols, particularly at night, and ensure efficient lighting across campus to deter theft.